Introducing Literacy Culture Through Illustrated Card Games To Improve Children’s Early Reading Skills - Suhartati; Hendra; Syahru Ramadhan (Jurnal Manajemen dan Inovasi Pembelajaran, 2026)
This study was motivated by children’s low early reading skills, as evidenced by their difficulties in recognizing letters, understanding syllable sounds, and reading simple words and sentences. Before the implementation of the illustrated card game, observation results showed that only a small proportion of children were able to recognize letters and read simple texts: only 40% of children could recognize letters, 48% could identify sounds and syllables, 36% could read words and sentences, 52% could understand the content of what they read, and 44% demonstrated a positive attitude and interest in reading. This situation indicates that the children’s early reading skills are still low and that there is a need for engaging learning strategies tailored to their characteristics. This study is a descriptive qualitative research, with the primary data sources being teachers and students at KB Al Muchtaddin. Data were collected through observation, interviews, and documentation during the implementation of literacy culture introduction activities. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research results showed a significant improvement following the implementation of illustrated card games. After the activities were conducted, the children’s abilities improved significantly: letter recognition reached 88%, sound and syllable recognition 80%, reading words and sentences 76%, comprehension of reading material 92%, and attitudes toward and interest in reading 84%. These improvements indicate that the illustrated card game medium is effective in fostering a culture of literacy while strengthening the early reading skills of children at KB Al Muchtaddin.